A comparative study of intravenous ferricarboxymaltose and double dose oral iron therapy in treatment of anemia in pregnancy - G., Greeshma; C. S., Beeresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: During pregnancy, iron deﬁciency is due to an imbalance between demand and supply, this worsens as pregnancy advances, according to CDC (centres for disease control and prevention) anemia is defined as Hb concentration lesser than 11 gm/dl in the first and third trimesters, and/or lesser than 10.5 gm/dl in the second trimester. Methods: The prospective comparative study was planned with the objective to assess the effectiveness of intravenous ferricarboxymaltose and oral double dose iron in treating anaemia in pregnant women. This study was conducted from January 2019 to June 2020 among 100 (50 in each group) pregnant anemic women attending a rural tertiary care centre. Results: This comparative study between double dose oral iron and i.v. iron treatment showed, hemoglobin levels improved at comparable rate across both treatments, however significantly more women achieved anemia correction with ferric carboxymaltose than oral iron More women achieved significant improvement in Hb with single dose of ferric carboxymaltose, whereas with oral iron additional dose of iron supplementation was required. Treatment related adverse reactions were seen more which oral iron treatment than with FCM. With markedly higher rates of gastrointestinal disorders. Conclusions: FCM is comparable more effective and better tolerated than oral iron treatment in pregnant women. Rapid correction of anemia was seen with i.v. FCM, thus in late stage pregnancy, when time to delivery is a limiting step, administration of FCM may be a more appropriate option than oral iron for rapid and effective anemia correction.